Production and single step purification of cyclodextrin glycosyltransferase from alkalophilic bacillus firmus by ion exchange chromatography - Savergave, Laman S.; Mule, Santosh S.; Jogdand, Vitthal V.; Nene, Sanjay N.; Gadre, Ramchandra V. (Biochemical Engineering Journal, 2008)
Production and purification of starch digesting cyclodextrin glycosyl transferase (CGTase) from alkalophilic Bacillus firmus was investigated. Fermentation was carried out in 141 bioreactor at 28 degrees C using a medium containing dextrin, yeast extract, peptone, (NH4)H2PO4 and MgSO4.7H(2)O. The extracellular enzyme was concentrated by tangential flow ultrafiltration. The concentrated enzyme was chromatographed using DEAE-sepharose and phenyl sepharose. DEAE-sepharose could be used to purify CGTase in a single step with 23.1 fold purification and 80.6% recovery. The enzyme obtained had homogeneity and the molecular weight was 76 kDa confirmed by SDS-PAGE. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alkalophilic; Bacillus firmus; CGTase; cyclodextrin; Purification